Imatinib and everolimus in patients with progressing advanced chordoma: A phase 2 clinical study. Issue 20 (14th September 2018) - Stacchiotti, Silvia; Morosi, Carlo; Lo Vullo, Salvatore; Casale, Alessandra; Palassini, Elena; Frezza, Anna Maria; Dinoi, Gabriella; Messina, Antonella; Gronchi, Alessandro; Cavalleri, Adalberto; Venturelli, Elisabetta; Morelli, Daniele; et al.
Abstract : Background: We present the results of an academic phase 2 study on imatinib plus everolimus in patients who have progressive advanced chordoma. Methods: In January 2011, 43 adult chordoma patients were enrolled in the study and received imatinib 400 mg/day and everolimus 2.5 mg/day until progression or limiting toxicity. Eligible patients had progressed in the 6 months before study entry. PDGFRB, S6, and 4EBP1 expression and phosphorylation were evaluated by way of immunohistochemistry and/or western blotting. The primary endpoint was the overall response rate (ORR) according to Choi criteria. Secondary endpoints were RECIST 1.1 response, progression‐free survival (PFS), overall survival (OS), correlation between S6/4EBP1 phosphorylation and response. Results: Thirteen of 43 patients were pretreated with imatinib. Among 40 of the 43 patients who were evaluable by Choi criteria, the best responses were 9 with partial response (ORR, 20.9%), 24 with stable disease (SD) (ORR, 55.8%), and 7 with progressive disease (ORR, 16.3%). Forty‐two patients were evaluable by RECIST criteria, with 1 partial response (ORR, 2.3%), 37 stable disease (ORR, 86%), and 4 progressive disease (ORR, 9.3%). The median PFS according to Choi criteria was 11.5 months (range, 4.6‐17.6 months), and 58.8% and 48.1% of patients were progression‐free at 9 and 12 months, respectively. The median PFS by RECIST criteria was 14 months; the median OS was 47.1 months. When assessable, S6/4EBP1 was phosphorylated in a high and moderate/low proportion of tumor cells in responsive and nonresponsive patients, respectively. Toxicity caused a temporary and definitive treatment discontinuation in 60.5% and 30.2% of patients, respectively. Conclusions: Imatinib plus everolimus showed a limited activity in progressing advanced chordoma. Interestingly, the amount of tumor cells activated for mammalian target of rapamycin effectors correlated with the response. Toxicity was not negligible. Abstract : In this phase II clinical trial, imatinib plus everolimus showed limited activity in patients affected by progressive advanced chordoma, with a response rate by Choi of 20.9% and an 11.5‐month median PFS. Interestingly, responses were observed also in patients with secondary resistance to imatinib monotherapy and correlated with PFS, survival, and the amount of tumor cells activated for S6 and/or 4EBP1.